2016
DOI: 10.1007/s00217-016-2823-9
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of mushrooms for production of food biofortified with lithium

Abstract: investigated mushroom species in various cultures as food or alternative medicines, their Li-biofortified forms could potentially find social acceptance. The concentrations of Li accumulated in fruiting bodies were not high enough for application in psychiatric treatments but could potentially support the daily intake of Li for behavior modification or health beneficiary purposes. Further studies are necessary to fully investigate the safety implications of Li-enriched mushrooms for humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
2
22
0
1
Order By: Relevance
“…The REEs values of honeysuckle are in agreement with those reported by our previous report, 18 and the REEs levels of the rest of the fl owers were not found in literature. The levels of REEs in most measured fl ower samples were similar to the values of green tea leaf (Camellia sinensis L.) 12,19 from China and wild mushroom from Poland, 20 and were much higher than the values of rice and wheat 21 that was consider to be a main source of dietary REEs in China. 19 and navel orange 23 from China.…”
Section: Resultssupporting
confidence: 65%
“…The REEs values of honeysuckle are in agreement with those reported by our previous report, 18 and the REEs levels of the rest of the fl owers were not found in literature. The levels of REEs in most measured fl ower samples were similar to the values of green tea leaf (Camellia sinensis L.) 12,19 from China and wild mushroom from Poland, 20 and were much higher than the values of rice and wheat 21 that was consider to be a main source of dietary REEs in China. 19 and navel orange 23 from China.…”
Section: Resultssupporting
confidence: 65%
“…A novel challenge in agriculture is the production of tailored foods, i.e., foods specifically suitable for target groups of people with particular nutritional needs. In fact, in recent years, a number of studies have highlighted the possibility of producing vegetables for specific physiological conditions, such as biofortified vegetables, with the aim of counteracting different nutritional deficits [1][2][3][4][5][6][7][8]. In general, these authors reported evidence on the use of specific growing protocols aimed to increase the content of specific nutrients in plant tissues, such as iodine (I), silicon (Si), calcium (Ca), selenium (Se), zinc (Zn), and iron (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can be used in biofortification strategies in mushroom cultivation and result in their increased nutritional value or biological activity. A number of studies have already demonstrated that this approach can be employed to enrich the fruiting bodies of selected species with elements such as copper in Ganoderma lucidum [4]; iron (Fe) in Pleurotus ostreatus, P. cornucopiae, P. djamor, P. pulmonarius or P. djamor v. roseus [5]; lithium (Li) in G. lucidum, P. eryngii and P. ostreatus [6,7]; potassium (K) in P. eryngii, Flammulina velutipes or Hypsizygus marmoreus [8]; selenium (Se) in A. bisporus, P. eryngii, P. ostreatus, Pholiota nameko [9,10] and zinc (Zn) in G. lucidum and P. ostreatus [11]. Particular attention has been paid to substrate supplementation with inorganic Se salts as such an approach appears to potentially increase antioxidant, immunomodulatory and anticancer activities of selected mushrooms species [12,13].…”
Section: Introductionmentioning
confidence: 99%